Functional ecology characteristics of key community-forming aquatic and semi-aquatic plant species in Teletskoye Lake (Republic of Altai, Russia) - Laura M. Kipriyanova; Diana V. Sityaeva; Sergei A. Rosbach (Acta Biologica Sibirica)
This study explores five primary morpho-functional traits – photosynthetic canopy height, leaf mass, leaf area, specific leaf area, and seed mass – of 17 community-forming species of aquatic and semiaquatic plants in Teletskoye Lake: Alopecurus aequalis, Caltha palustris, Carex acuta, C. vesicaria, Eleocharis palustris, Equisetum fluviatile, Myriophyllum sibiricum, Petasites radiatus, Ranunculus reptans, Ranunculus trichophyllus, Potamogeton alpinus, Potamogeton × cognatus, P. gramineus, P. maackianus, P. perfoliatus, P. praelongus, Subularia aquatica. The greatest leaf mass and area were observed in the hygrohelophyte Caltha palustris and the helophyte Petasites radiatus, whereas the smallest were noted in the miniature amphibious plants – Subularia aquatica and Ranunculus reptans. The highest specific leaf area (SLA) values (leaf area per unit mass) were found in true aquatic plants – hydrophytes. The macrophytes from the Potamogetonaceae family, which are characterized by endozoochoric dispersal, showed the highest seed mass indices, while the primarily hydrochoric annuals such as Alopecurus aequalis and Subularia aquatica displayed the lowest. Statistically significant differences were identified in SLA between floating and submerged leaves in the Potamogetonaceae family, notably between Potamogeton alpinus and Potamogeton gramineus, with submerged leaves showing significantly higher SLA values than floating leaves.